High-Density Lipoprotein Cholesterol in Young Nondiabetic Coronary Heart Disease Patients - Ziyang Hu; Jingle Cui; Xueshan Li; Yaohui Zhou; Lu Cai; Shibin Zhang (Cardiology Research and Practice)
Objective. To investigate the association between the lipid profiles and coronary heart disease (CHD) in nondiabetic patients younger than 65 years of age. Method. 424 patients were enrolled in this study from January 2019 to December 2020. All the patients were screened for clinically indicated coronary angiography. They were divided into two groups according to the coronary angiography results: 340 patients with the presence of CHD (at least one coronary artery stenosis ≥50%) were classified as the CHD group, and the rest with the absence of CHD comprised the normal group. The demographic data and lipid profiles were compared. Result. CHD was higher in males than females (84.5% vs. 62.2%, P<0.001). In the CHD group, the level of high‐density lipoprotein cholesterol (HDL-C) was lower P<0.001, while the triglyceride (TG)/HDL-C ratio was higher P=0.022. No significant differences were shown between the two groups in terms of age, family history of CHD, hypertension, and the levels of TC, TG, and LDL-C. Gender differences were further explored. In men, except for the level of HDL-C which was significantly lower in the CHD group than that in the normal group P=0.017, parameters were comparable. A binary logistic regression model further indicated that HDL-C was associated with CHD (OR = 0.137, 95%CI: 0.031–0.594, P=0.008). Also, with the increase of the number of coronary artery with lesions, the levels of HDL-C decreased significantly in men. In women, no differences were observed between the CHD group and normal group. Conclusion. HDL-C may be inversely associated with the risk of CHD in young nondiabetes patients, especially in men. More research is needed to confirm it.